An infectious chimeric human immunodeficiency virus type 2 (HIV-2) expressing the HIV-1 principal neutralizing determinant. - Mamounas, M (1995)
The human immunodeficiency virus type 1 strain MN (HIV-1MN) principal neutralizing determinant (PND, V3 loop) was introduced into infectious molecular clones HIV-2KR and simian immunodeficiency virus mm239 (SIVmm239) by hybridization PCR, replacing the corresponding HIV-2 or SIV envelope cysteine loops with the HIV-1 coding sequence. The HIV-2 chimera (HIV-2KR-MNV3) was found to be capable of infecting a number of T-cell lymphoblastic cell lines as well as primary peripheral blood mononuclear cells. In contrast, the SIV chimera (SIV239MNV3) was not replication competent. Envelope produced by HIV-2KR-MNV3 but not the parental HIV-2KR was recognized by V3-specific and HIV-1-specific polyclonal antisera in radioimmunoprecipitation assays. HIV-2-specific antisera recognized both the chimeric and parental virus but not HIV-1MN. The chimeric HIV-2KR-MNV3 virus proved to be exquisitely susceptible to neutralization by HIV-1-specific and V3-specific antisera, suggesting the potential for use in animal models designed to test HIV-1 vaccine candidates which target the PND.